(untitled) (Al-Academy, 2016)
The media guide is a small-sized printed medium, whose importance is highlighted through the specific information it carriesThe task of the guide lies in the clarity of these indications and making a positive impact on the recipient with understanding so it is a means for the purpose of reaching the effect and effectiveness of the message symbols from the movements of lines in which elements that are supposed to be equal in the performance of their functions and the purpose of their existence gather to achieve the mental response of perception, understanding and enjoyment. It must be in an objective unity based on the balance in this distribution. To form a formal organizational unit and an integrated system, the result of which is to give the distinct phenotypic character to systems that have their various balances according to the nature of these systems.